The role of government in implementation of innovations: a case of Lithuania - Tvaronavičienė, Manuela; Korsakienė, Renata (Business: Theory and Practice, 2007)
The paper deals with factors fostering implementation of innovations into Lithuanian economy. Size of enterprises and sectors of economy have been taken into account. The authors strive to estimate the role of government in the process of innovation in the economy. Hence, authors analyse factors fostering implementation of innovations, the role of state aid and perceived efficiency of state policy. At the end of the paper, the results of the survey are summarized and the conclusions are presented. Presented investigation is based on questioning results of business enterprises.